The time evolution of the social cost of carbon: An application of fund - David Anthoff; Steven Rose; Richard S. J. Tol; Stephanie Waldhoff (Kiel Institute for the World Economy (IfW), 2011)
The authors estimate the growth rate of the social cost of carbon. This is an indication of the optimal rate of acceleration of greenhouse gas emission reduction policy over time. The authors find that the social cost of carbon increases by 1.3% to 3.9% per year, with a central estimate of 2.2%. Previous studies found an average rate of 2.3% and a range of 0.9 to 4.1%. The rate of increase of the social carbon depends on a range of factors, including the pure rate of time preference, the rate of risk aversion, equity weighting, the socioeconomic and emission scenarios, the climate sensitivity, dynamic vulnerability, and the curvature of the impact functions.
Keywords: Q54; 330; social cost of carbon